STRATEGI PEMBELAJARAN GURU RISALATUL MAHID DALAM MEMBANGUN PEMAHAMAN MATERI ISTIHADHAH SANTRI PUTRI PONDOK PESANTREN DARUL ULUM AL-FADHOLI MERJOSARI MALANG - Nur Azizatus Solikhah; Rosichin Mansur; Moh Eko Nasrullah (VICRATINA, 2020)
The researcher formulated the problem, namely about the learning proceses of female students regarding about istihadhah material in the book Risalatul Mahid, and the understanding of female students regarding istihadhah material in the book Risalatul Mahid. This istihdahah is something that is naturally experienced by some women, but not many know how to punish and how to purify when going to perform the right worship according to Islamic law. The reasearch was conducted with a qualitative approach ant type of case study reaserch. Data collection procedures were carried out using participatory observation methods, unstructured interviews and documentation metods, data analysis techniques used are data presentataion, conclusions and verfication. Cheking the validity of the data used is source triangulation, technical triangulation, and peer discusions. In the lerarning process there are 3 stages namely the first planning before leraning begins, secondly implementation using the leecture and questions and answer method, and using expository strategies, and the third is the evaluation of reading the book Risalatul mahid. And Ula A’s students’ understanding of istihadhah is quite good, although it is not yet maximal.